Conservation policies, scientific research and the production of Lake Pátzcuaro's naturecultures in Postrevolutionary México (1920–1940). (July 2022) - Aguilera Lara, Jahzeel
Abstract: The Lake Pátzcuaro region has recently been a focus of attention of various scholars working in the field of cultural studies. These works have highlighted the role of Lake Pátzcuaro in creating a national culture and identity during the postrevolutionary period in México (1920–1940). However, the cultural production of nature has not been subject to the same attention. Taking a cultural and historical geography approach, the paper considers the production of Lake Pátzcuaro's 'naturecultures' during the postrevolutionary period in México. This is how discourses about culture and identity shaped nature and vice versa. The emphasis is on what I call scientific cultures of nature, referring to ideas and practices around nature that made use of scientific claims. The goal is to understand the role of these practices in shaping Lake Pátzcuaro as a meaningful discursive assemblage, and the relationship between this process and nation-state building. I do this by examining the discourses surrounding the establishment of environmental protection schemes in Lake Pátzcuaro, comprising the creation of a 'forest hydrological reserve' and fishing regulations, and the introduction of species to protect native fish and improve fisheries. I argue that these actions took part in broader efforts to create México and the Mexican, contributing to the naturalization of narratives about the nation. Highlights: Examines the mutual production of Lake Pátzcuaro naturecultures. Explores the role of nature in the definition of national identity in México. Examines the development of scientific research and conservation policies. Considers narratives around the notions of the hybrid, the native and the exotic.